The fundamental goal of wound prevention: recent best evidence - Emily Haesler, & Nicoletta Frescos and & Robyn Rayner & (Wound Practice and Research, 2018)
Preventing wounds is a fundamental goal for all wound professionals and is enshrined within the Australian national wound management standards. The paper presents an overview of the recent evidence in the prevention of venous leg ulcers, pressure injuries, diabetes-related foot ulcers and skin tears. Recent literature searches identified a paucity of high-quality evidence for most wound prevention interventions. The paper presents evidence available to support current best practice. Despite the lack of strong scientific evidence, fundamental care interventions, including promoting healthy skin integrity and off-loading pressure, continue to be mainstay in preventing wounds of all aetiology.